Safety of PRRSV-2 MLV vaccines administrated via the intramuscular or intradermal route and evaluation of PRRSV transmission upon needle-free and needle delivery - Adthakorn Madapong (Nature Portfolio, 2021)
Abstract Two distinct experiments (Exp) were conducted to evaluate the shedding and efficacy of 2 modified live porcine reproductive and respiratory syndrome virus (PRRSV) type 2 vaccines (MLV) when administered intramuscularly (IM) or intradermally (ID) (Exp A), and the potential of PRRSV transmission using a needle-free device (Exp B). One-hundred fifty-four, 3-week-old castrated-male, pigs were procured from a PRRSV-free herd. In Exp A, 112 pigs were randomly allocated into 4 groups of 21 pigs including IM/Ingelvac MLV (G1), IM/Prime Pac (G2), ID/Prime Pac (G3), and non-vaccination (G4). Twenty-eight remaining pigs were served as non-vaccination, age-matched sentinel pigs. G1 was IM vaccinated once with Ingelvac PRRS MLV (Ing) (Boehringer Ingelheim, Germany). G2 and G3 were IM and ID vaccinated once with a different MLV, Prime Pac PRRS (PP) (MSD Animal Health, The Netherlands), respectively. Following vaccination, an antibody response, IFN-γ-SC, and IL-10 secretion in supernatants of stimulated PBMC were monitored. Sera, tonsils, nasal swabs, bronchoalveolar lavage, urines, and feces were collected from 3 vaccinated pigs each week to 42 days post-vaccination (DPV) and assayed for the presence of PRRSV using virus isolation and qPCR. Age-matched sentinel pigs were used to evaluate the transmission of vaccine viruses and were introduced into vaccinated groups from 0 to 42 DPV. Seroconversion was monitored. In Exp B, 42 pigs were randomly allocated into 5 groups of 3 pigs each including IM/High (T1), ID/High (T2), IM/Low (T3), ID/Low (T4), and NoChal. Twenty-seven remaining pigs were left as non-challenge, age-matched sentinel pigs. The T1 and T2, and T3 and T4 groups were intranasally challenged at approximately 26 days of age with HP-PRRSV-2 at high (106) and low (103 TCID50/ml) doses, respectively. At 7 days post-challenge, at the time of the highest viremia levels of HP-PRRSV-2, T1 and T2, and T3 and T4 groups were IM and ID injected with Diluvac Forte using needles and a need-less device (IDAL 3G, MSD Animal Health, The Netherlands), respectively. Same needles or needle-less devices were used to inject the same volume of Diluvac Forte into sentinel pigs. Seroconversion of sentinels was evaluated. The results demonstrated that PP vaccinated groups (G2 and G3), regardless of the route of vaccination, had ELISA response significantly lower than G1 at 7 and 14 DPV. PP-vaccinated groups (G2 and G3) had significantly higher IFN-γ-SC and lower IL-10 secretion compared to the Ing-vaccinated group (G1). The two different MLV when administered intramuscularly demonstrated the difference in virus distribution and shedding patterns. PP-vaccinated pigs had significantly shortened viremia than the Ing-vaccinated pigs. However, ID-vaccinated pigs had lower virus distribution in organs and body fluids without virus shedding to sentinel pigs. In Exp B, regardless of the challenge dose, sentinel pigs intradermally injected with the same needle-less device used to inject challenged pigs displayed no seroconversion. In contrast, sentinel pigs intramuscularly injected with the same needle used to inject challenged pigs displayed seroconversion. The results demonstrated the transmission of PRRSV by using a needle, but not by using a needle-less device. In conclusion, our results demonstrated that ID vaccination might represent an alternative to improve vaccine efficacy and safety, and may be able to reduce the shedding of vaccine viruses and reduce the iatrogenic transfer of pathogens between animals with shared needles.